A Tale of Two Cities (and Three Men): Armenians in Rome and Ancona, 1560s‑1580s - Cesare Santus (Diasporas: Circulations, Migrations, Histoire)
The essay examines the settlement patterns of members of an Eastern Christian diaspora, the Armenians, in late 16th‑century Ancona and Rome. The commercial appeal of the former is illustrated by the case of the Armenian merchant Giorgio Moratto, while the diplomatic and cultural centrality of Rome is embodied by Marco Antonio Abagaro, the son of an Armenian ambassador to the Pope, who later became an interpreter, translator and printer for the Roman curia. These two types of mobility came together thanks to the representative of a third, main vector of circulation, which was primarily religious in nature: Giulio Antonio Santori, cardinal of Santa Severina, used Moratto’s money and Marco Antonio Abagaro’s work to build a church and hospice for Armenian pilgrims in Ancona (1580), on the model of the one established in Rome a few years earlier. By comparing the common features and the different developments of the Armenian hospices in Rome and Ancona, this article aims to stimulate reflection on the characteristics of early modern Catholic confessional mobility and its relationship with other channels of mobility in the early modern Mediterranean.